2009
DOI: 10.2337/db08-0376
|View full text |Cite
|
Sign up to set email alerts
|

Vessel Shrinkage as a Sign of Atherosclerosis Progression in Type 2 Diabetes

Abstract: OBJECTIVE-The aim of this study was to determine the natural history of vascular remodeling of atherosclerotic plaques in patients with type 2 diabetes and the predictors of vessel shrinkage.RESEARCH DESIGN AND METHODS-In this serial intracoronary ultrasound (IVUS) study, 237 coronary segments from 45 patients enrolled in the DIABETES I, II, and III trials were included. Quantitative volumetric IVUS analyses (motorized pullbacks at 0.5 mm/s) were performed in the same coronary segment after the index procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…41 Thus, variations in α-1 and α-2 chains of type IV collagen regulate the capacity of arterial remodeling and determine stiffness, aneurysm formation, etc. This knowledge in combination with our observation of increased amounts of these collagen chains in T2DM therefore fits well with the novel idea that basement membrane accumulation may constitute at least part of the molecular background for increased arterial stiffness, 11 dysfunctional remodeling, 12,13 and increased protection against abdominal aneurysms, 14,15 which prevails in DM. Another striking observation in the present study is the reduced levels of many of the upregulated basement membrane proteins in the subgroup of type 2 diabetic patients treated with metformin.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…41 Thus, variations in α-1 and α-2 chains of type IV collagen regulate the capacity of arterial remodeling and determine stiffness, aneurysm formation, etc. This knowledge in combination with our observation of increased amounts of these collagen chains in T2DM therefore fits well with the novel idea that basement membrane accumulation may constitute at least part of the molecular background for increased arterial stiffness, 11 dysfunctional remodeling, 12,13 and increased protection against abdominal aneurysms, 14,15 which prevails in DM. Another striking observation in the present study is the reduced levels of many of the upregulated basement membrane proteins in the subgroup of type 2 diabetic patients treated with metformin.…”
Section: Discussionsupporting
confidence: 85%
“…7,8 Moreover, in a study based on RNA-microarray examinations of nonatherosclerotic arterial tissue from T2DM patients, we found altered expression of a matrix-related pathway 9 and increased expression of the basement membrane protein fibulin-1, both at the mRNA and protein level, in arterial samples from patients with T2DM. 10 Alterations in the arterial matrix could be involved in the increased arterial stiffness, 11 in the dysfunctional remodeling (shrinkage instead of compensatory enlargement of damaged arteries), 12,13 and in the paradoxically decreased risk of abdominal aortic aneurysms described among patients with T2DM. 14,15 Likewise, altered arterial matrix influence atherogenesis 16 and alter responses to injury.…”
mentioning
confidence: 99%
“…Interestingly, previous investigators have consistently reported an association between greater residual plaque burden at reference vessel segments and edge stenosis in the cohorts of sirolimuseluting, paclitaxel-eluting, and bare metal stent implantation. 24, 25 Coupled with the rapid progression of remote or other atherosclerotic lesions and higher incidence of comorbidities in patients with DM, these factors may explain to some degree the higher incidence of future clinical events, even in the DES era, as described by others. 23 In this study, despite achieving a similar lumen area, lesions in patients with DM showed significantly greater asymmetric stent expansion than non-DM lesions and there was a significant relationship between SEI and NUS in the overall population.…”
Section: Study Limitationsmentioning
confidence: 98%
“…23 Additionally, DM patients more often have smaller reference vessels because of diffuse atherosclerosis and inadequate compensatory remodeling. [24][25][26] These plaque characteristics, coupled with smaller, less compliant reference vessels may be responsible for the smaller lumen area at postprocedure in DM patients. In this study, mechanical factors, such as lumen area at postprocedure, maximum balloon diameter, and maximum balloon pressure were independently associated with in-stent follow-up lumen, and the association of lumen area at postprocedure with the follow-up lumen in both in-stent and reference segments seemed to be the strongest, as assessed from the t statistic value in the multiple regression analysis.…”
Section: Vessel Response In Diabetes Versus Nondiabetesmentioning
confidence: 99%